Extended use of systemic steroid is beneficial in preserving hearing in guinea pigs after cochlear implant. (1st December 2016) - Rah, Yoon Chan; Lee, Min Young; Kim, Shin Hye; Kim, Doo Hee; Eastwood, Hayden; O'Leary, Stephen J.; Lee, Jun Ho
Abstract: Conclusion: Seven-day administration of systemic steroids was more effective in preserving hearing for 12 weeks after cochlear implantation (CI) than a 3-day delivery. Objectives: To determine the effectiveness of extended delivery of systemic steroids to preserve hearing in guinea pigs after CI. Methods: Dexamethasone (4 mg/ml) was delivered parenterally via a mini-osmotic pump for either 3 or 7 days. A dummy CI electrode was inserted via cochleostomy approach in 8-week-old guinea pigs. Auditory thresholds were assessed from tone burst auditory brainstem responses (2, 8, 16, 24, and 32 kHz) at 1 day prior to CI, and 1, 4, and 12 weeks after implantation. Histologic evaluation of the cochleae was carried out. Results: No differences were observed in hearing thresholds among groups before CI. Significant hearing preservation was achieved at 8, 16, 24, and 32 kHz only in the 7-day infusion group compared with the control group at 1 week after CI. The same trend was maintained at 4 weeks (16, 24 kHz) and 12 weeks (16, 24, and 32 kHz). Histologic review of the 7-day infusion group revealed less fibrosis and ossification in the scala tympani and the preservation of more spiral ganglion cells, compared with the control group.